Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Hi, can someone please help, and possibly explain the answer please.

Hi Can Someone Please Help And Possibly Explain The Answer Please class=

Sagot :

Answer:

[tex]x=\frac{-(-2)\±\sqrt{(-2)^2-4(3)(0)} }{2(3)}[/tex]

Step-by-step explanation:

Quadratic formula: [tex]x=\frac{-b\±\sqrt{b^2-4ac} }{2a}[/tex] when the equation is [tex]0=ax^2+bx+c[/tex]

The given equation is [tex]1=-2x+3x^2+1[/tex]. Let's first arrange this so its format looks like [tex]y=ax^2+bx+c[/tex]:

[tex]1=-2x+3x^2+1[/tex]

[tex]1=3x^2-2x+1[/tex]

Subtract 1 from both sides of the equation

[tex]1-1=3x^2-2x+1-1\\0=3x^2-2x+0[/tex]

Now, we can easily identify 3 as a, -2 as b and 0 as c. Plug these into the quadratic formula:

[tex]x=\frac{-b\±\sqrt{b^2-4ac} }{2a}\\x=\frac{-(-2)\±\sqrt{(-2)^2-4(3)(0)} }{2(3)}[/tex]

I hope this helps!